Leveling up English: The impact of digital gamified learning on tertiary EFL students’ motivation and performance - Ayiz, Abdul; Suryo Priyatmojo, Arif; Aulia, Widya (Indonesian Journal of Education and Pedagogy, 2025)
The integration of digital gamified learning has emerged as a transformative pedagogical innovation in higher education, particularly in English as a Foreign Language (EFL) instruction. This study examined the effect of gamified learning platforms, specifically Quizizz, on tertiary-level EFL students’ motivation and academic performance. Employing a quasi-experimental design, 80 undergraduate students were assigned to either an experimental group (n = 40), which received instruction through gamified activities, or a control group (n = 40), which engaged in conventional learning methods. Data were obtained through pre- and post-tests alongside a standardized motivation scale. Independent samples t-tests demonstrated that the experimental group significantly outperformed the control group in both motivation (t(78) = 4.52, p < .001) and performance (t(78) = 5.11, p < .001). The results indicated a substantial improvement in the experimental group’s post-test scores (M = 85.47, SD = 4.62) compared to the control group (M = 78.15, SD = 5.08). Similarly, motivational levels increased markedly, with higher mean ratings reported by the experimental cohort. These findings underscore the efficacy of digital gamification as a pedagogical tool to enhance learner engagement and achievement in EFL contexts. The study not only reinforces the relevance of integrating gamified approaches in tertiary language education but also provides empirical evidence for their role in sustaining motivation and improving performance.